Working characteristics for practising dental hygienists in two countries in different hemispheres. Issue 2 (14th September 2021) - Olson, Hanna; Ratnayake, Jithendra; Veerasamy, Arthi; Quaranta, Alessandro; Meldrum, Alison
Abstract: Objectives: The study aimed to collect and compare practising characteristics for dental hygienists (DHs) in New Zealand (NZ) and Sweden. Methods: Dental hygienists from NZ and Sweden were invited to participate in an anonymous online survey focussing on their working practices. An email, with a link to the online survey and a participant information sheet, was sent to DHs registered with their professional association in their respective country. Frequency analyses and cross‐tabulations were conducted using chi‐square and Fisher's exact tests to investigate possible statistical associations to allow for comparisons between the countries. Results: DH is a female‐dominated workforce with equal distribution of gender in both countries. The majority of DHs in NZ worked in private practice while Swedish DHs mostly worked in the public sector. NZ participants were younger and with a more recent qualification than their Swedish counterparts. The highest degree of education was a PhD for DHs working in Sweden, compared with a master's degree for NZ participants. The majority of participants from both countries treated patients 65 years of age or older, with the most common medical conditions being cardiovascular disease and diabetes mellitus. The most common dental condition observed/treated was periodontal disease. Over 60% agreed to have an understanding of information technology (IT). The most used technical equipment was digital radiology, followed by other diagnostic tools. Conclusion: Findings confirm previous international data on demographical uptake for the DH workforce in NZ and Sweden. A coherence was seen in patient characteristics, DHs' attitudes towards information technology and use of technical equipment.